Comparative Analysis of Cystolithalopexy and Percutaneous Cystolithotripsy in Senior Pediatric Population Aged 6 to 15 Years - Tariq Ahmad, Sher Wali Khan, Muhammad Tayyib, Mohammad Yasir Khalily (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Objectives: To compare cystolithalopexy and percutaneous cystolithotripsy in children 6 to 15 years based on complications. Methodology: The study includes 100 patients under the age of 6 to 15 years age, split into two groups called Group-A (45) and Group B. (55). Included were those patients with stones that were smaller than 20 mm in size (on average, 14 mm). Patients in Group-A received cystolithalopexy therapy utilizing a ureteroscope and a pneumatic lithoclast assisted by a Dormia basket. Patients in Group B received percutaneous cystolithotripsy therapy. Results: The age range of the 100 male pediatric patients ranged from 6 to 15 years (mean age 8 years). The average length of stay in the hospital was 2.5 days for patients in Group A and 3 to 8 days for patients in Group B. Patients in Group-A exhibited higher rates of urinary tract infections (8%) and urethral injuries (22%), residual stones (1%), enlarged bladders (2.2%), urinary retention (4.4%), and fever (13.33%). While in Group B, 18% of the members experienced urinary tract infections, 5% wound infections, 4% hematuria, 7% bladder size enlargement, and 27% fever. In each Group, urine retention was 7%. Conclusion: Pediatric male patients with vesicle calculus respond substantially better to cystolithalopexy because it requires less invasive surgery, leaves no scar, and has fewer complications. Keywords: Bladder Calculus, Comparison, Cystolithalopexy, Ureteroscope, Pneumatic Lithoclast, Dormia basket, percutaneous cystolithotripsy.